EXTH-43. DYNAMIC MULTI-OMICS ANALYSIS OF MLN4924-TREATED GLIOBLASTOMA CELLS REVEALS ABSENCE OF PTEN AS A CANDIDATE DRIVER OF NEDDYLATION INHIBITION RESISTANCE. (11th November 2019) - Taylor, Brett; Ferdosi, Shayesteh; Bybee, Rita; Tang, Nanyun; Peng, Sen; Garcia-Mansfield, Krystine; David-Dirgo, Victoria; Sharma, Ritin; Pirrotte, Patrick; Berens, Michael; Dhruv, Harshil
Abstract: Glioblastoma multiforme (GBM) is the most lethal primary brain tumor and calls for novel therapeutic development. The neddylation pathway may be a therapeutic target, as global over activation of neddylation has been found in GBM patients and has correlated with shorter patient survival. Analogous to ubiquitination in reaction scheme and enzyme classes used, neddylation is a post-translational modification that is essential to many protein regulation and biological processes. Although non-cullin NEDD8 substrates have been investigated in recent years, the most well-characterized substrates of neddylation are the cullin subunits of Cullin-RING ligases (CRLs), which act as a scaffold for substrates to be ubiquitinated and degraded. The neddylation inhibitor MLN4924 targets NEDD8 Activating Enzyme (NAE), an upstream activator of neddylation, and induces cell cycle arrest, apoptosis and senescence in cancer cells. In this work, we investigated the context of vulnerability to Pevonedistat (MLN4924) in GBM. Efficacy of MLN4924 in glioma cell models was evaluated by measuring cell viability (CellTiterGlo®), colony formation efficiency, and cell cycle progression (flow cytometry with propidium iodide staining). GB1 (IC50 = 0.28 μM), LN18 (IC50 = 0.19 μM), and GBM43 (IC50 = 0.45 μM) were established as sensitive and M059K (IC50 = 5.5 μM), SNU1105 (IC50 = 20.9 μM), and GBM39 (IC50 = 10.3 μM) as non-sensitive cell lines based on IC50 values. To discover genomic and/or proteomic markers of differential response, we collected RNA and protein from sensitive and non-sensitive cell lines after 0, 2, 8 and 24 hour treatment with MLN4924 for RNA sequencing and mass spectroscopy analyses. Multi-OMICS data point towards the absence of functional PTEN as a driver of MLN4924 resistance. Uncovering the mechanism underlying GBM's vulnerability to MLN4924 will expand the knowledge of neddylation's role in cancer and may arm physicians with an understanding of whether a GBM patient would respond to MLN4924 treatment or not.